Pelatihan Pembuatan Pupuk Organik pada Kelompok Masyarakat Kepenghuluan Bagan Sinembah Timur - Andi Irfan; Dessyka Febria; Desrir Miftah; Indrawati Indrawati; Febri Rahmi (Asosiasi Dosen Akuntansi Indonesia, 2021)
Community service aims to introduce and train community groups to be able to make organic fertilizer using household waste. This training was carried out at the Bagan Sinembah Timur Community Group (Pokmas). Pokmas were formed by the Kepenghuluan to advance the people's economy. Introduction and training on how the community uses household waste that no longer has economic value to turn it into organic fertilizer. This training is expected to reduce the community's dependence on inorganic fertilizers. Training on Making Organic Fertilizer in thet Bagan Sinembah Timur Community Group using participatory learning methods. In its implementation, the Bagan Sinembah Timur Kepenghuluan Community Group was very enthusiastic in participating in this training to become organic fertilizer, after the training they were immediately able to practice making fertilizer independently. The organic fertilizer produced will help the community to further increase agricultural yields and can help farmers in the scarcity of fertilizers.